Penguatan Nilai Budaya Minang “Sumbang Duo Baleh” Bagi Siswi Melalui Kegiatan Forum Annisa di MAN 2 Bukittinggi - Muhammad Nur Hadi Rasyid; Khairuddin Khairuddin; Jasmienti Jasmienti; Charles Charles (CV. Aksara Global, 2024)
This research aims to understand and analyze the strengthening of Minang cultural values